8M Demonstrations, the Spanish Far Right, and the Pandemic in a Hybrid Media System - Aurora Labio-Bernal; Laura Manzano-Zambruno (Media and Communication, 2023)
For years, the construction of social subjectivity has been conditioned by the role of the so-called mass media, but the multiplicity of media platforms today contributes to the configuration of reality. In this context, this study analyses how the discourse of the far right in Spain effectively criminalised the International Women’s Day (8M) demonstrations in the first year of the pandemic by linking them to an increase in Covid-19 infections. To implement this strategy, Spain’s far-right party, Vox, used its social media accounts, but it also had the support of ultra-conservative digital media outlets to legitimise its discursive distortions. Taking this into account, this article presents a content and critical discourse analysis of the Twitter and Gab accounts operated by Vox and its leaders, Santiago Abascal and Rocio Monasterio, as well as three ultra-conservative newspapers, La Razón, OK Diario, and Libertad digital. The period covered is from 8 March 2020 to 8 March 2021.